2014
DOI: 10.1039/c3sm52761a
|View full text |Cite
|
Sign up to set email alerts
|

Segmental relaxation behavior of polystyrene chains in the cores of collapsed dry micelles tethered on the micelle film surface by a poly(acrylic acid) corona

Abstract: We present an experimental investigation of the segmental relaxation behavior of polystyrene (PS) chains that are confined in a micellar core tethered by a poly(acrylic acid) (PAA) block corona on the dry film surface, along with various core density and molecular weight of PS block from below to well above the entanglement molecular weight. The results show that the onset temperature of PS chain rearrangement (T(onset)), which was much lower than the T(bulk)(g) of the corresponding PS block and higher than T(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…1d), which are slightly lower than the value obtained from DLS. This is possibly due to the shrinkage of the particles in the dry state 64,65 or because of overestimation of the particle size in DLS, as here the average size is measured by taking into account the hydration shells around the particles. The morphology was further supported by atomic force microscopy images (AFM), which showed nearspherical nanostructures with the average height and width in the range of 6-16 nm and 100-120 nm, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1d), which are slightly lower than the value obtained from DLS. This is possibly due to the shrinkage of the particles in the dry state 64,65 or because of overestimation of the particle size in DLS, as here the average size is measured by taking into account the hydration shells around the particles. The morphology was further supported by atomic force microscopy images (AFM), which showed nearspherical nanostructures with the average height and width in the range of 6-16 nm and 100-120 nm, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of the concentration of casting solution on surface dynamics of the corresponding spin-coated PMMA lms Contact angle measurement is one of the most effective and sensitive methods for studying surface reconstruction and chain relaxation. 19,57,58,69,70 The apparent activation energy (E a ) for the surface relaxation of uorine-labeled PMMA lms prepared from various concentrations of casting solutions was examined on the basis of the time-temperature superposition principle for chain dynamics. The above results showed that variation in contact angle on PMMA lms aer being annealed was attributed to changes in chemical components on the lm surface.…”
Section: Resultsmentioning
confidence: 99%
“…The micelles were prepared according to our previously reported method. 19 The amphiphilic block copolymers were completely dissolved in dioxane at a concentration of 0.5 wt % and then filtered through a 0.45 μm porous polytetrafluoroethylene (PTFE) film. Subsequently, Milli-Q water was slowly added to the solution to induce aggregation of the PS or PMMA chains.…”
Section: Methodsmentioning
confidence: 99%
“…The sum frequency generation (SFG) spectra of the micelle film were obtained using a custom-designed EKSPLA SFG spectrometer described previously. 19 The morphology of single micelles was observed on an Ultra 55 scanning electron microscope (SEM) (Zeiss, Germany) and a Multimode 8 AFM (Bruker Co., Germany). Phase image and height image of micelles were obtained using AFM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation